Graphene composite conductive glass fiber material as well as preparation method and application thereof

By using chemical vapor deposition method to grow graphene and amorphous carbon composite films on the surface of glass fiber materials, the problem that existing materials do not meet the needs in high-surface resistance scenarios is solved, and wider resistance regulation is achieved and higher Water resistance and longer material life.

CN119430690APending Publication Date: 2025-02-14BEIJING GRAPHENE INST +2

Patent Information

Application Number
CN202411708593.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing graphene composite conductive glass fiber materials do not meet the needs in high-surface resistance scenario applications, and graphene is prone to fall off, and lacks water resistance and wear resistance, resulting in unstable electrical heating elements.

Method used

The graphene and amorphous carbon composite film were grown on the surface of glass fiber material by chemical vapor deposition. By adjusting the components of graphene and amorphous carbon, the surface resistance range of the composite film was adjusted, and the water resistance and density of the material were improved.

Benefits of technology

The adjustment range of surface resistance is expanded, the water resistance and shear strength of the composite film are improved, and the functional stability and material life of the electric heating device are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430690A_ABST
    Figure CN119430690A_ABST
Patent Text Reader

Abstract

The invention relates to a graphene composite conductive glass fiber material and a preparation method and application thereof, the graphene composite conductive glass fiber material comprises a conductive composite film and a glass fiber material substrate, the composite film conformally coats the surface of the glass fiber material substrate, and the composite film is composed of graphene and an amorphous carbon material. According to the invention, the strength of the composite film coating the glass fiber tows is improved, the composite film is not easy to fall off, the compactness and water resistance in the film are increased, the shear strength is greatly improved, and the adjustment range of surface resistance can be expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of conductive materials, and in particular to a graphene composite conductive glass fiber material and a preparation method and application thereof. Background Art

[0002] At present, the main methods for preparing graphene are graphite exfoliation, epitaxial growth, graphite oxidation and chemical vapor deposition. Chemical vapor deposition is the most widely used technology for depositing a variety of materials in the semiconductor industry. In theory, it introduces two or more gaseous raw materials into a reaction chamber, and then they react chemically with each other to form a new material, which is deposited on the substrate surface.

[0003] Combine graphene with traditional glass fiber engineering materials to form graphene composite conductive glass fiber materials. Graphene has very good conductivity. The surface resistance of the conductive glass fiber fabric coated with graphene film is low, which is difficult to meet the application requirements of some high surface resistance scenarios; the combination of graphene and glass fiber materials is a weak van der Waals force, which makes graphene easy to fall off, seriously affecting the subsequent process yield; the commonly used graphene is a few-layer polycrystalline graphene, which has many defects and low density. These characteristics determine that the graphene composite conductive glass fiber material has poor water resistance and weak wear resistance. When it is used for electric heating materials, the resistance will change with temperature due to water resistance problems, which will cause the heating element to be unstable and cannot be designed and manufactured. Although polymer materials are coated on the surface of the glass fiber cloth on which graphene is grown, the graphene layer can be protected, but the electrical properties of the graphene glass fiber cloth cannot be regulated. Therefore, further improving its special electrical properties through composite means is still a hot topic of research.

[0004] CN115613162B discloses a composite fiber, comprising a core fiber, a graphene layer covering the core fiber, and a hexagonal boron nitride layer covering the outside of the graphene layer, wherein the graphene layer and the hexagonal boron nitride layer are directly grown by chemical vapor deposition. The method has complicated procedures. First, the graphene layer needs to be deposited first, and then the hexagonal boron nitride layer is deposited, and when preparing the boron nitride layer, it is necessary to ensure that the reaction process does not damage the existing graphene layer; secondly, the boron nitride layer prepared by this process cannot regulate the final electrical properties of the material.

[0005] CN117286712A discloses a composite fiber and a preparation method thereof. The composite fiber includes an alumina fiber and a graphene carbon material layer formed on the surface of the alumina fiber, and the carbon material layer includes graphene and / or graphite. The composite fiber of this invention is obtained by direct growth through chemical vapor deposition. This patent uses alumina fibers that can withstand higher temperatures as a substrate, which is more expensive. In addition, the graphene carbon material layer formed on the surface of the alumina fiber is composed of graphene and / or graphite, which will result in a lower resistance of the prepared composite fiber and a smaller adjustable range of resistance. Moreover, the membrane layer of the composite membrane prepared by this patent has poor wear resistance, and the cost of the composite fiber material is very high due to the price of the alumina fiber itself, which limits the application scenarios.

[0006] CN108545966A "A graphene glass fiber and its preparation method" provides a graphene glass fiber and its preparation method, wherein the graphene glass fiber is composed of a graphene layer formed on the surface of the glass fiber by a chemical vapor deposition method and a glass fiber in the core. The preparation method is a chemical vapor deposition method. The graphene layer includes 1-4 layers of graphene, and the glass fiber includes a glass fiber bundle, a glass fiber cloth, a glass fiber filament, a glass fiber mat or a glass fiber fabric. The method prepares 1-4 layers of graphene on the surface of the glass fiber, and the number of graphene layers is limited, resulting in a resistance control range of 5000 to 20000Ω / cm, a small control range, and the graphene layer is unprotected, and the interlayer shear resistance is weak. It is easy to be damaged in actual application, resulting in changes in electrical properties.

[0007] The present application proposes to use chemical vapor deposition to grow a graphene and amorphous carbon composite film on the surface of a glass fiber material that can be conformally coated on the surface of a glass fiber bundle. By adjusting the components of graphene and amorphous carbon, the surface resistance range of the graphene composite conductive glass fiber material can be adjusted within a larger range, so that it can be used in a wider range of application scenarios. It can also adjust the water resistance and density of the composite film, thereby improving the functional stability as an electric heating device and increasing the life of the material. Summary of the invention

[0008] Based on the above problems, the technical problem to be solved is a composite conductive layer formed of graphene and amorphous carbon. By adjusting the process parameters, the surface resistance of the composite film can be adjusted by adjusting the ratio of graphene to amorphous carbon in the composite film, thereby overcoming the above-mentioned defects such as the small resistance control range and insufficient thermal stability of the graphene film layer.

[0009] The present invention provides an inventive point: a graphene composite conductive glass fiber material, including a composite film for conduction and a glass fiber material substrate, the composite film is conformally coated on the surface of the fiber bundle of the glass fiber material substrate, and the composite film is composed of graphene and amorphous carbon material.

[0010] Furthermore, in the composite film, the sp 2 The proportion of hybridization is 5% to 15%;

[0011] Furthermore, the control range of the surface resistance of the composite film is 20-20000Ω / sq.

[0012] Another invention provided by the present invention is a method for preparing a graphene composite conductive glass fiber material, characterized in that the steps are as follows:

[0013] 1) Pre-treat the surface of the glass fiber material;

[0014] 2) A chemical vapor deposition method is used to set the pressure range in the process chamber to 200-5000 Pa, the temperature range to 500-1100° C., the flow ratio of the carbon source to the carrier gas to (100-2000):(150-4000), the carbon source and the carrier gas are introduced to directly deposit and grow a composite film on the surface of a glass fiber material substrate, and the composite film is conformally coated on the surface of the fiber bundle of the glass fiber material substrate and is sleeved on the glass fiber bundle in a cylindrical shape to obtain a graphene composite conductive glass fiber material, and the deposition time is 20-2000 min.

[0015] Furthermore, during the pretreatment in step 1), the glass fiber material is subjected to a heat treatment process, and when the temperature is set at 200°C to 600°C, it is kept warm for 2 to 72 hours at a time, or when the first temperature is set at 200°C to 350°C, it is kept warm for 2 to 30 hours, and when the second temperature is set at 350°C to 600°C, it is kept warm for 1 to 10 hours.

[0016] Further, the carbon source in step 2) is selected from at least one of methane, ethylene, acetylene, propane and propylene;

[0017] The carrier gas is selected from hydrogen or argon.

[0018] Preferably, step 2) further comprises an additive, wherein the additive is selected from at least one of methanol, ethanol and acetone, and the ratio of the additive to the carbon source is (80-400): (150-4000).

[0019] Further, the growth in the chemical vapor deposition (CVD) process is selected from dynamic growth and static growth.

[0020] Furthermore, the chemical vapor deposition method is selected from LPCVD, APCVD, PECVD, preferably LPCVD.

[0021] Preferably, when PECVD is used, the carbon source is subjected to plasma treatment before entering the high temperature zone of 500°C to 1100°C. The plasma may be one of radio frequency plasma, direct current plasma and pulse plasma.

[0022] The third invention point provided by the present invention is: an electric heating component composed of the above-mentioned graphene composite conductive glass fiber material and the graphene composite conductive glass fiber material prepared by the above-mentioned preparation method can be used in the fields of heating, heating, drying, physical therapy and anti-icing.

[0023] Compared with the prior art, the advantages of the present invention are:

[0024] The conductive glass fiber material of the graphene and amorphous carbon material composite film in the present invention adopts a simple CVD method to prepare a composite material composed of a graphene-amorphous carbon composite film coating a glass fiber bundle, which not only improves the strength of the composite film coating the glass fiber bundle, making it not easy to fall off, but also increases the density and water resistance inside the film, greatly improves the shear strength, and can also expand the adjustment range of the surface resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Graphene and amorphous carbon materials (sp 2 Raman spectrum of the composite film (accounting for 12.98%);

[0026] Figure 2 Graphene and amorphous carbon materials (sp 2 Raman spectrum of the composite film (accounting for 5.87%);

[0027] Figure 3 XPS test value diagram of graphene and amorphous carbon material composite film;

[0028] Figure 4 Graphene and amorphous carbon material composite film sp 2 and sp 3 Density diagram of different contents;

[0029] Figure 5 Water resistance of graphene and amorphous carbon material composite films.

[0030] Specific implementation method

[0031] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below. However, it should be understood that the description here is only used to explain the present application and is not used to limit the scope of the present application.

[0032] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present application, and the terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The reagents and instruments used herein are all commercially available, and the characterization means involved can refer to the relevant descriptions in the prior art, which will not be repeated herein.

[0033] In order to further understand the present application, the present application is further described in detail below in conjunction with the best embodiment.

[0034] Example 1

[0035] This embodiment provides a graphene composite conductive glass fiber material, including a composite film for conduction and a glass fiber material substrate, wherein the composite film is conformally coated on the surface of the glass fiber material substrate, and the composite film is composed of graphene and amorphous carbon material.

[0036] Conformal coating refers to a coating method in which the coating layer is attached to the surface of the carrier and fits with the carrier to maintain the shape of the carrier. In the same plane, graphene is connected together by small domains, and multiple graphene domains are connected by sp 2 and sp 3 Randomly distributed amorphous carbon connects graphene domains to each other. Between different layers, amorphous carbon is dominant and connected to the graphene layer. When there is only graphene, the graphene and the glass fiber are bonded by van der Waals force. Since the graphene layer is thin and flexible, the graphene layer is easily damaged. If graphene and amorphous carbon are mixed and grown, the graphene can be wrapped due to the high hardness of amorphous carbon. Although the glass fiber is still bonded by van der Waals force, the overall hardness of the grown graphene-amorphous carbon layer is much higher than that of graphene, so it is not easy to be damaged, thereby improving the damage resistance of the composite film, so the bonding between the composite film layer and the glass fiber bundle is enhanced.

[0037] Amorphous carbon, also known as transition carbon, is a large category of carbon allotropes. Amorphous carbon refers to carbon materials with a very low degree of graphitization and crystallization, which are close to amorphous forms (or have no fixed shape and periodic structural regularity).

[0038] Glass fiber material is a hydrophilic material that easily absorbs water in a humid air environment. Perfect single-crystal graphene has excellent water vapor barrier properties, but graphene generally prepared by chemical vapor deposition often has various crystal defects such as dislocations and grain boundaries, and multi-layer graphene or graphite has a large interlayer spacing, and its density and water resistance are poor. After being made into a heating element, its heating temperature is easily changed due to the adsorption of water vapor.

[0039] The glass fiber of the present application is glass fiber bundle, glass fiber cloth, glass fiber yarn, glass fiber mat or glass fiber fabric. The diameter of the glass fiber is 5 to 20 μm.

[0040] According to the composition, glass fiber can be divided into quartz fiber cloth, high silica fiber, medium silica fiber, high strength fiber, high modulus fiber, alkali-free glass fiber, etc.

[0041] The bonding between graphene and the glass fiber substrate is a Van der Waals force, which is weak; composite film formation with amorphous carbon materials can not only achieve conformal coating with the glass fiber bundle, but also prevent the problem of easy slippage between multi-layer graphene layers, thereby improving the wear resistance and non-falling characteristics of the coating. Few-layer graphene, especially polycrystalline graphene, has many defects, weak interlayer bonding, and low density, resulting in weak water resistance and shear strength; after composite with amorphous carbon materials, the film layer is thicker and more dense, and the water resistance and shear strength are greatly improved.

[0042] As a further preferred embodiment, in the composite film, the sp 2 The hybridization ratio is 5% to 15%, such as 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or any value between any two values;

[0043] The graphene and amorphous carbon materials of the present invention do not contain sp hybridization, so the composite film consists of only sp 2 and sp 3 Hybridization mode, namely sp 2 Add sp 3 The total ratio is 1, where sp 2 The ratio is as above. 2 The hybridization ratio is obtained by XPS test analysis, such as Figure 3 As shown in Table 1.

[0044] Table 1 XPS test results

[0045] PEAK Energy(eV) Chemical state Weight % C1s 283.92 <![CDATA[sp 2 ]]> 5.87 C1s 285.02 <![CDATA[C-C(sp 3 )]]> 94.13

[0046] As a further preferred embodiment, the control range of the surface resistance is 20-20000Ω / sq.

[0047] Graphene has good conductivity, and the surface resistance of the conductive glass fiber material coated with graphene film is low, which does not meet the application requirements. The coating compounded with amorphous carbon material can expand the adjustment range of surface resistance.

[0048] The ratio of graphene and carbon-based material composite membrane can be controlled by changing the flow ratio, pressure, temperature of the carbon source and carrier gas and adding alcohols, ketones or water containing oxygen functional groups.

[0049] Example 2

[0050] Based on Example 1, an electric heating component composed of the above-mentioned graphene composite conductive glass fiber material and the conductive glass fiber material prepared by the above-mentioned preparation method can be used in the fields of heating, heating, drying, physical therapy and anti-icing.

[0051] Example 3

[0052] According to the content of this application, the preparation method of the graphene composite conductive glass fiber material of Example 1 is prepared, and the steps are as follows:

[0053] 1) The surface of the glass fiber material is pretreated first. The purpose of the pretreatment is to remove the surface wetting agent or coupling agent to expose the original surface of the glass fiber;

[0054] 2) A chemical vapor deposition method is used to set the pressure range in the process chamber to 200-5000 Pa, the temperature range to 500-1100° C., the flow ratio of the carbon source to the carrier gas to (100-2000):(150-4000), the carbon source and the carrier gas are introduced to directly deposit and grow a composite film on the surface of a glass fiber material substrate, and the composite film is conformally coated on the surface of the fiber bundle of the glass fiber material substrate and is sleeved on the glass fiber bundle in a cylindrical shape to obtain a graphene composite conductive glass fiber material, and the deposition time is 20-2000 min.

[0055] As a further preferred embodiment, during the pretreatment in step 1), the glass fiber material is subjected to a heat treatment process, and when the temperature is set at 200°C to 600°C, it is kept warm for 2 to 72 hours at a time, or when the first temperature is set at 200°C to 350°C, it is kept warm for 2 to 30 hours, and when the second temperature is set at 350°C to 600°C, it is kept warm for 1 to 10 hours.

[0056] As a further preferred embodiment, the carbon source in step 2) is selected from at least one of methane, ethylene, acetylene, propane, and propylene; the carbon source flow rate is 100 to 2000 sccm;

[0057] The carrier gas is selected from hydrogen or argon; the carrier gas flow rate is 150 to 4000 sccm;

[0058] As a preferred embodiment, step 2) further includes an additive, wherein the additive is selected from at least one of methanol, ethanol, and acetone, and the ratio of the additive to the carbon source is (80-400): (150-4000).

[0059] Methanol, ethanol, acetone, etc. are both carbon sources and weak oxidants, and are introduced in trace amounts during the growth process.

[0060] As a further preferred embodiment, the growth in the CVD process is selected from dynamic growth and static growth.

[0061] Dynamic growth: A roll of glass fiber cloth wound on a plastic cylinder is mounted on the unwinding shaft of the unwinding chamber of the roll-to-roll CVD equipment, and then one end of the glass fiber cloth is passed through the process chamber and fixed on the plastic cylinder of the unwinding roller in the unwinding chamber. The process is that when the temperature, pressure, and process gas flow in the process chamber are stable, the unwinding shaft rotates counterclockwise, the winding chamber rotates clockwise, and the glass fiber cloth is continuously transmitted and moved in the process chamber at a certain speed parallel to the axis of the process chamber until the glass fiber cloth on the unwinding shaft is completely released. In this process, the process chamber and the glass fiber cloth have relative movement.

[0062] Static growth: After the glass fiber cloth is cut, stacked, wound, and bent into a fixed shape, thickness, and volume, it is pushed into the process chamber of the CVD equipment through a carrier and kept stationary. During the process, when the temperature, pressure, and process gas flow in the process chamber are stable, the gas penetrates into the surface of each strand of the glass fiber cloth to grow. In this process, there is no relative movement between the glass fiber cloth and the process chamber.

[0063] As a further preferred embodiment, the chemical vapor deposition method is selected from LPCVD, APCVD, PECVD, preferably LPCVD.

[0064] Preferably, when PECVD is used, the carbon source is subjected to plasma treatment before entering the high temperature zone of 500°C to 1100°C. The plasma may be one of radio frequency plasma, direct current plasma and pulse plasma.

[0065] LPCVD or low pressure chemical vapor deposition is widely used for the deposition of carbon materials, oxides, nitrides, and polysilicon.

[0066] APCVD, or atmospheric pressure chemical vapor deposition, refers to a chemical vapor deposition method performed under 1 atmosphere, which is the original method used for chemical vapor deposition. This process requires a simple system and a fast reaction speed, but has poor uniformity and poor step coverage, so it is generally used for thick layer dielectric deposition.

[0067] PECVD generally refers to plasma enhanced chemical vapor deposition, which is a preparation method that uses glow discharge in a deposition chamber to ionize the substrate and then undergoes a chemical reaction on the substrate to deposit semiconductor films or other material films.

[0068] Embodiment 4:

[0069] According to the content of this application, the graphene composite conductive glass fiber material of this application is specifically described. If no specific experimental steps or conditions are specified in the embodiments, the conventional experimental steps or conditions described in the literature in this field can be used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional reagent products that can be purchased commercially.

[0070] The present invention is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed by the present invention.

[0071] Experimental Group 1

[0072] The preparation method of the graphene composite conductive glass fiber material of Example 1 is as follows:

[0073] 1) The surface of the glass fiber material is pretreated at 400°C for 60 hours to remove the surface wetting agent or coupling agent to expose the original surface of the glass fiber;

[0074] 2) Using the LPCVD method, the pressure in the process chamber was set to 1000Pa, the temperature to 950℃, the dissolved acetylene as the carbon source, the flow rate was 250sccm, the carrier gas was hydrogen, the flow rate was 1000sccm, the carbon source was introduced to directly grow a composite film on the surface of the glass fiber material substrate, and dynamic growth was used for deposition for 15min to obtain a graphene composite conductive glass fiber material, in which the sp of CC 2 The hybridization ratio is 12.98%, and the Raman spectrum is as follows Figure 1 shown.

[0075] Test results: The surface resistance of graphene composite conductive glass fiber cloth is 3012Ω / sq.

[0076] Experimental Group 2

[0077] The preparation method is roughly the same as that of experimental group 1, using static growth. The experimental conditions are shown in Table 1.

[0078] Test results: The surface resistance of graphene composite conductive glass fiber cloth is 25Ω / sq.

[0079] Experimental Group 3

[0080] The preparation method is roughly the same as that of experimental group 1, using static growth. The experimental conditions are shown in Table 1.

[0081] Test results: The surface resistance of graphene composite conductive glass fiber cloth is 611Ω / sq.

[0082] Experimental Group 4

[0083] The preparation method was roughly the same as that of experimental group 1, using dynamic growth. The experimental conditions are shown in Table 1.

[0084] Test results: The surface resistance of graphene composite conductive glass fiber cloth is 3008Ω / sq.

[0085] Experimental Group 5

[0086] The preparation method is roughly the same as that of experimental group 1, using static growth. The experimental conditions are shown in Table 1.

[0087] Test results: The surface resistance of graphene composite conductive glass fiber cloth is 1010Ω / sq.

[0088] Experimental Group 6

[0089] The preparation method is roughly the same as that of experimental group 1, using the PECVD method, plasma treatment, radio frequency plasma, dynamic growth, experimental conditions are shown in Table 1, and Raman spectra are shown in Figure 2 shown.

[0090] Test results: The surface resistance of graphene composite conductive glass fiber cloth is 11332Ω / sq.

[0091] Experimental Group 7

[0092] The preparation method is roughly the same as that of experimental group 1, using the PECVD method, plasma treatment, radio frequency plasma, and static growth. The experimental conditions are shown in Table 1.

[0093] Test results: The surface resistance of graphene composite conductive glass fiber cloth is 19750Ω / sq.

[0094] Experimental Group 8

[0095] The preparation method was roughly the same as that of experimental group 1, with methane being used as the carbon source. The experimental conditions are shown in Table 1.

[0096] Test results: The surface resistance of graphene composite conductive glass fiber cloth is 3056Ω / sq.

[0097] Comparative Example 1

[0098] The preparation method was roughly the same as that of experimental group 1, with methane being used as the carbon source. The experimental conditions are shown in Table 1.

[0099] Test results: The surface resistance of graphene composite conductive glass fiber cloth is 3350Ω / sq.

[0100] Comparative Example 2

[0101] The conductive film layer in the graphene conductive glass fiber material is only graphene, in which the sp2 hybridization ratio of CC is 52.45%, and the adjustable surface resistance range is 100-5000Ω / sq.

[0102] Table 1 Surface resistance of graphene composite conductive glass fiber materials

[0103]

[0104]

[0105] Effect group 1

[0106] Figure 4 For different SP 2 Graphene conductive glass fiber cloth with high content, Figure 4 A is the glass fiber material of experimental group 3, SP 2 The content is 12.98%, SP 2 The conductive glass fiber cloth with a high content of graphene has a smooth and uniform surface of the tow; Figure 4 B is the glass fiber material of experimental group 4, SP 2 The content is 5.87%, SP 2 Conductive glass fiber cloth with low graphene content has a rough surface of the fiber bundles.

[0107] Effect group 2

[0108] Figure 5 A represents the glass fiber material of Comparative Example 1, the sp 2 The content is 17.53%. As the time of exposure to air increases, the sp 2 Conductive glass fibers with high content will absorb moisture in the air, causing the square resistance of the conductive glass fibers to decrease from a maximum of 3500Ω / sq to 2750Ω / sq, a decrease of 21.42%. This material has poor water resistance and its square resistance continues to decrease, indicating that water absorption causes the square resistance to decrease. Subsequent heating to remove moisture will restore the square resistance to its original value.

[0109] Figure 5 B is the glass fiber material of experimental group 4, the sp 2 The content is 5.87%, and the sp 3 Conductive glass fibers with a high content of water are difficult to absorb moisture in the air, so the square resistance of the glass fibers fluctuates irregularly, ranging from 3000Ω / sq to 3200Ω / sq. This indicates that the material has good water resistance, because the irregular fluctuation of the square resistance data may be caused by test errors.

[0110] Experiments show that graphene has good conductivity, but the surface resistance of the coated graphene film is low, which does not meet the application requirements. The glass fiber material of the composite film of graphene and other carbon-based materials of the present invention can expand the adjustment range of surface resistance; the film layer of the composite film is thicker, denser, and has better water resistance.

[0111] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A graphene composite conductive glass fiber material, comprising a composite film for conduction and a glass fiber material substrate, characterized in that: The composite film is conformally coated on the surface of the glass fiber material substrate, and the composite film is composed of graphene and amorphous carbon material.

2. The graphene composite conductive glass fiber material according to claim 1, characterized in that: In the composite film, the sp 2 The hybridization accounts for 5% to 15%.

3. The graphene composite conductive glass fiber material according to claim 1, characterized in that: The surface resistance of the composite film can be adjusted in the range of 20-20000Ω / sq.

4. A method for preparing the graphene composite conductive glass fiber material according to any one of claims 1 to 3, characterized in that: Here are the steps: 1) Pre-treat the surface of the glass fiber material; 2) A chemical vapor deposition method is used to set the pressure range in the process chamber to 200-5000 Pa, the temperature range to 500-1100° C., the flow ratio of the carbon source to the carrier gas to (100-2000):(150-4000), the carbon source and the carrier gas are introduced, and a composite film is directly deposited and grown on the surface of the glass fiber material substrate, and the composite film is conformally coated on the surface of the fiber bundle of the glass fiber material substrate, and finally is sleeved on the glass fiber bundle in a cylindrical shape, so as to obtain a graphene composite conductive glass fiber material, and the deposition time is 10-2000 min.

5. The preparation method according to claim 4, characterized in that: The pretreatment process in step 1) is as follows: the glass fiber material is kept at a temperature of 200° C. to 600° C. for 2 to 72 hours at a time; or, The glass fiber material is first kept at 200°C to 350°C for 2 to 30 hours, and then kept at 350°C to 600°C for 1 to 10 hours.

6. The preparation method according to claim 4, characterized in that: The carbon source in step 2) is selected from at least one of methane, ethylene, acetylene, propane and propylene; and the carrier gas is selected from hydrogen or argon.

7. The preparation method according to claim 4, characterized in that: Step 2) further includes an additive, wherein the additive includes at least one of methanol, ethanol, and acetone, and the ratio of the additive to the carbon source is (80-400): (150-4000).

8. The preparation method according to claim 4, characterized in that: The growth in the chemical vapor deposition process is selected from dynamic growth and static growth.

9. The preparation method according to claim 4, characterized in that: The chemical vapor deposition method is selected from LPCVD, APCVD, PECVD, preferably LPCVD. Preferably, when PECVD is used, the carbon source is subjected to plasma treatment before entering the high temperature zone of 500° C. to 1100° C., and the plasma is one of radio frequency plasma, direct current plasma, and pulse plasma.

10. An electric heating component made of the graphene composite conductive glass fiber material according to any one of claims 1 to 3 and the graphene composite conductive glass fiber material prepared by the preparation method according to any one of claims 4 to 9 can be used in the fields of heating, heating, drying, physical therapy and anti-icing.

Citation Information

Patent Citations

  • Graphene glass fiber and preparation method thereof

    CN108545966A

  • Composite fiber and preparation method and application thereof

    CN117286712A

Cited By

  • Heating deicing graphene glass fiber cloth and preparation method thereof

    CN121295421A